PEMBERDAYAAN KELOMPOK TANI MELALUI PEMBUATAN PUPUK ORGANIK LIMBAH KOTORAN TERNAK DAN SABUT KELAPA - Dian Eka Kusumawati; Istiqomah Istiqomah; Siti Shoimah; Avia Nur Kholifah; Devi Nur Mayang Sari (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2023)
Livestock manure is the end result of a livestock business that must be managed properly and with benefits. If not treated properly will result in waste and environmental pollution. The large amount of livestock manure waste in Mangkujajar Village has not been utilized properly and has the potential to pollute the environment. In addition to livestock manure which cannot be utilized optimally, there is quite a large amount of coconut waste due to the increasing demand for coconut consumption. The purpose of community service activities is to increase the knowledge and skills of the community and farmers regarding the processing of livestock manure and coconut coir into useful organic fertilizer. Community service was carried out from June to August 2023 in Mangkujajar Village, Kembangbahu District, Lamongan Regency which was attended by local village Farmer Groups. Service activities carried out are observation and outreach, delivery of training materials, practice of making organic fertilizer, and evaluation. The results of the community service activities show that the participants have increased their knowledge and skills in processing waste into organic fertilizer, participants can also make organic fertilizer independently to meet the fertilizer needs of farmers and also have economic value that can increase the income of farmers. Besides that, it can also realize a sustainable farming system by using organic ingredients and minimizing the use of chemicals.